As relações entre história e ficção no romance Agosto, de Rubem Fonseca - Keler, Adriana (2019)
By the end of the 20th Century, historical fiction had an increase of number of books and a different approach by the authors which led to an enrichment and diversity of the genre. This work studies the novel Crimes of August, by Rubem Fonseca, published in 1990. The narrative brings side by side the events of a tragic moment of Brazilian History and an investigation of a murder in Rio de Janeiro. It is, at the same time, a thriller and a historical fiction. On August 24th, 1954, the president of Brazil, Getúlio Vargas, accused of being responsible for the attempted assassination of his political opponent, the journalist Carlos Lacerda, committed suicide. During the investigation of a murder, the police officer will connect history and fiction when he includes a security guard of the president among the suspects. This work focuses in studying how historical and fictional events are related in the novel, in order to study Crimes of August as historical fiction.